Cancer Prevention in Low-Resource Countries: An Overview of the Opportunity - Kamaraju, Sailaja (Am Soc Clin Oncol Educ Book, 2020)
Rising trends in the incidence of cancer in low- and middle-income countries (LMICs) add to the existing challenges with communicable and noncommunicable diseases. While breast and colorectal cancer incidence rates are increasing in LMICs, the incidence of cervical cancer shows a mixed trend, with rising incidence rates in China and sub-Saharan Africa and declining trends in the Indian subcontinent and South America. The increasing frequencies of unhealthy lifestyles, notably less physical activity, obesity, tobacco use, and alcohol consumption are causing a threat to health care in LMICs. Also, poorly developed health systems tend to have inadequate resources to implement early detection and adequate basic treatment. Inequalities in social determinants of health, lack of awareness of cancer and preventive care, lack of efficient referral pathways and patient navigation, and nonexistent or inadequate health care funding can lead to advanced disease presentation at diagnosis. This article provides an overview of opportunities to address cancer control in LMICs, with a focus on tobacco control, vaccination for cervical cancer, novel tools to assist with early detection, and screening for breast and other cancers.